PREDICAMENTS IN THE ARCHITECTURE AND DESIGN EDUCATION (TURKEY AS AN EXAMPLE) - Tunalı, Selma; Öztekin, Kamuran (European Scientific Journal, ESJ, 2015)
Architectural education −as the world’s oldest design oriented vocational training− is being tried to improved in our country dependent on the central enforcing institutions. Due to this situation, educational institutions that have devoted themselves for centuries to raising salutary and distinctive generations in this profession have become unsuccessful. Disregard for an intense and a supervised information obtaining process that should be applied in universal standards, the qualitative weakness of the legislation and the rules and the acceptance of the quality of the current vocational graduation in design education as adequate, have caused a significant decrease in the value of the offered structures and designs. In an educational environment where the modern education is unfulfilled and the institutions that offer education in architecture, interior design, urban planning are destroyed and the traditional behavior and universal knowledge is not observed, future dynamics of professions remain inadequate. When all these responsibilities are carried out by only one unifying and rule-making administration, and when chambers as nongovernmental organizations try to stay away from the common, contemporary, universal and liberal education policies, a vocational formation in which conceptual developments never mature is created. The enforcing and the repressive administration system is trying to adapt a traditional education model that is consentient to the students’ current capabilities (never requiring more) in our education system. Expecting a low-level success −and being contended with that success− from students who have no background in design, who have no conceptual intelligence, who are only middleschool graduates and who enter vocational education institutions by chance, and expect them to practice a profession that is creative, constructive and authentic should be considered a huge mistake. In this study, in the extent of the concrete reality of our country, we will examine the adverse developments in design education, the spacial insufficiencies, the difficulties in the training of teaching staff and repressive sanctions in education while considering the international contemporary design education systems and programs. We will also try to offer some options for solution.